Non-supervised breathing exercise regimen in women with fibromyalgia: A quasi-experimental exploratory study. (May 2019) - Tomas-Carus, Pablo; Garrido, María; Branco, Jaime C.; Castaño, María Yolanda; Gómez, María Ángeles; Biehl-Printes, Clarissa
Abstract: Objectives: To know the effectiveness and safety of non-supervised breathing exercise regimen by promoting patients' self-management, and to investigate if non-supervised breathing exercise regimen shows similar benefits to supervised regimen in improving pain and fibromyalgia (FM) impact on daily life. Material and methods: Fifty-one women with FM were assigned to: supervised breathing exercise regimen group, non-supervised breathing exercise regimen group, and control group. Pain thresholds tolerance on tender points and FM impact on daily life were evaluated. Results: After 12-weeks of breathing exercises statistical differences were not found between supervised and non-supervised regimen. However, supervised regimen showed additional improvements in pain thresholds tolerance and in pain-FIQ subscale. Conclusion: Our results suggest that performing a non-supervised breathing exercise program could be as safe and effective as the supervised regimen. However, it was observed that there could be a tendency of supervised exercise regimen to show additional benefits in terms of pain.